GEMMA and GEMINI, two dedicated mixed-signal ASICs for Triple-GEM detectors readout. (29th March 2016) - Pezzotta, A.; Croci, G.; Costantini, A.; Matteis, M. De; Tagnani, D.; Corradi, G.; Murtas, F.; Gorini, G.; Baschirotto, A.
Abstract: GEMMA and GEMINI, two integrated-circuit front-ends for the Triple-GEM detector are presented. These two ASICs aim to improve detector readout performance in terms of count rate, adaptability, portability and power consumption. GEMMA target is to embed counting, timing and spectroscopic measurements in a single 8-channel device, managing a detector capacitance up to 15 pF. On the other hand, GEMINI is dedicated to counting measurements, embedding 16 channels with a detector capacitance up to 40 pF. Both prototypes, fabricated in 130 nm and 180 nm CMOS respectively, feature an automatic on-chip calibration circuit, compensating for process/temperature variations.